Formulasi Dan Penentuan Nilai SPF Lip Balm Kombinasi Ekstrak Kulit Nanas (Ananas comusus L. Merr) dan Kulit Wortel (Daucus carota L.) - Sukamdi, Dyani Primasari; Nurjanah, Cut Intan Ayu; Harimurti, Sabtanti; Krisridwany, Annisa; Amid, Azura; Haresmita, Perdana Priya (Program Studi Farmasi-Fakultas Matematika dan Ilmu Pengetahuan Alam-Universitas Tulang Bawang, 2025)
Lips are susceptible to ultraviolet (UV) exposure because they lack melanin, sweat glands, and hair follicles. To protect and moisturize lips, lip balm is widely used; however, it generally contains synthetic ingredients that can cause side effects. Therefore, a safe and effective natural-based alternative is needed. Pineapple peel (Ananas comusus L. Merr.) contains flavonoids and tannins that function as natural sunscreens. In contrast, carrot peel (Daucus carota L.) is rich in β-carotene, vitamin E, and flavonoids with antioxidant and natural coloring properties. The combination of these ingredients is considered complementary and has the potential to be used as natural active components in lip balm formulations. This study aims to determine the formulation and SPF value of lip balms containing pineapple and carrot peel extracts as UV protection agents. Four formulations were prepared: F0 (0% extract), F1 (10% pineapple peel extract), F2 (10% carrot peel extract), and F3 (combination of both extracts). The evaluation included organoleptic testing, homogeneity testing, stability testing, determination of the melting point, pH measurement, and SPF testing. Data were analyzed using the Kruskal-Wallis test method. The results showed that all formulations met the characteristics of a good lip balm, with SPF values of 1.028, 8.791, 8.949, and 25.672, respectively. Formulation F3 showed the highest SPF value with “ultra” protection, indicating strong potential as a natural UV-protective lip balm. Keywords: Pineapple peel, carrot peel, lip balm, formulation, SPF value.